The Role of The Process of Knowledge Management In Building the Safety Culture - Karolina KOSTERA (Communications of International Proceedings, 2022)
This paper presents the basic issues related with the process of knowledge management in the context of building and developing the safety culture. As the purpose of her deliberations, the author decided to highlight the issue of human resources, specifically workers' intrinsic characteristics which, when developed and enhanced properly, can contribute to improving the conditions of work and, consequently, the work safety. Given the long-term, multidimensional and continuous character of the safety culture forming process, it is important to take technical, legal and organisational actions to achieve ever higher levels of satisfaction, mutual trust and sense of stability. This hold true specifically when one realises that the safety culture of an individual affects the safety culture of an organisation, which in turn determines the safety culture of the society.
Keywords: safety culture; knowledge management; prevention; OHS management system